Understanding public intentions to participate in protection initiatives for forested watershed areas using the theory of planned behavior: a case study of Cameron Highlands in Pahang, Malaysia - Anak Empidi, Arlixcya Vinnisa; Emang, Diana (MDPI AG, 2021)
The heavy emphasis on land-use changes to meet the needs for gross domestic product growth often causes deforestation, affecting forests’ capability to function as watershed areas properly. While land-use changes generate socioeconomics success, they also lead to environmental deterioration that puts public welfare at greater risk. This study employs the Theory of Planned Behavior (TPB) to evaluate the public’s behavioral intentions towards participation in the protection initiatives for the forested watershed areas in the mountainous region of Cameron Highlands in Pahang, Malaysia. Survey data were used to analyze the effects of TPB constructs on the public’s behavioral intentions. The results show that the public demonstrated readiness to comply with governmental rules concerning environment protection and were motivated to participate in the protection initiatives when there is social encouragement. This study finds that attitude significantly influences the public’s behavioral intention. This, therefore, indicates the importance of creating conditions to encourage the public’s behavioral beliefs towards protection initiatives that would ensure the sustainability of forested watershed areas. Overall, this study offers information on public participation that is useful to be integrated into a meaningful institutional framework when addressing challenging environmental issues caused by land-use changes that could imperil public welfare.